Paracoccidioidomycosis and Addison's syndrome – case report. (April 2023) - Lazzaretti, Glória Sulczinski; Sena, Letícia Maria de Conto; Corrêa, Allex; Navarini, Daniel; Marcolan, Ana Maria; Reichert, Paulo Roberto
Paracoccidioidomycosis is caused by a fungus ( Paracoccidioides brasiliensis ), which is endemic to Brazil. It is most frequently found in the lungs, with haematogenous and lymphatic spread. The condition is more prevalent in men, between 30 and 60 years old, commonly rural workers. It is the third leading cause of death among chronic infectious diseases today. The systemic disease has an insidious and nonspecific course, with adrenal involvement being observed in 5% of cases and requiring the destruction of 80% of the glands for symptoms of adrenal insufficiency to appear. Isolated involvement of this gland is quite rare. In this case report, however, our patient presented wasting and adrenal insufficiency with isolated adrenal involvement by the fungus.